The rule of reflection over x-axis ⇒⇒⇒ (x,y)→(x,-y)
The rule of reflection over y-axis ⇒⇒⇒ (x,y)→(-x,y)
The rule of reflection over y = x ⇒⇒⇒ (x,y)→(y,x)
=================================================
let the coordinate of any point of the hexagon is (m,n)
The correct sequence will make the same coordinates
which mean start with (m,n) and the finish is also (m,n)
=================================================
Check option a- x-axis, y=x, x-axis, y=x
(m,n) → (m,-n) → (-n,m) → (-n,-m) → (-m,-n)
Wrong set of reflections
====================================================
Check option b- y-axis, x-axis, y-axis
(m,n) → (-m,n) → (-m,-n) → (m,-n)
Wrong set of reflections
=======================================================
Check option c- x-axis, y-axis, y-axis
(m,n) → (m,-n) → (-m,-n) → (m,-n)
Wrong set of reflections
=======================================================
Check option d- y=x, x-axis, y=x, y-axis
(m,n) → (n,m) → (n,-m) → (-m,n) → (m,n)
The correct set of reflections
=======================================================
So, the correct option is ⇒⇒ d- y=x, x-axis, y=x, y-axis